2011
DOI: 10.1159/000330032
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Licensed-Indication Use of Donepezil and Memantine Monotherapies for Treating Behavioural and Psychological Symptoms of Dementia in Patients with Alzheimer’s Disease: Systematic Review and Meta-Analysis

Abstract: Background/Aims: Behavioural and psychological symptoms of dementia (BPSD) in Alzheimer’s disease (AD) greatly increase caregiver burden. The abilities of donepezil and memantine to manage BPSD within their licensed indications in AD were compared. Methods: A systematic review, random effects meta-analysis and Bucher indirect comparison were conducted. Results: Six randomised controlled studies (4 donepezil and 2 memantine) reported use within the licensed indication and had Neuropsychiatric Inventory (NPI) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 87 publications
2
29
0
1
Order By: Relevance
“…To our knowledge, this is the first NMA of ChEIs treatment in patients with AD in which compared using both direct and indirect comparisons of interventions across trials simultaneously. This should strengthen the findings from our analysis over previous meta‐analyses (Trinh et al , 2003; Birks, 2006; Hansen et al , 2008; Lockhart et al , 2011;Tan et al , 2014; Wang et al , 2014). The study quality of head‐to‐head trials might be questionable, because two out of three head‐to‐head trials were not double‐blinded.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…To our knowledge, this is the first NMA of ChEIs treatment in patients with AD in which compared using both direct and indirect comparisons of interventions across trials simultaneously. This should strengthen the findings from our analysis over previous meta‐analyses (Trinh et al , 2003; Birks, 2006; Hansen et al , 2008; Lockhart et al , 2011;Tan et al , 2014; Wang et al , 2014). The study quality of head‐to‐head trials might be questionable, because two out of three head‐to‐head trials were not double‐blinded.…”
Section: Resultssupporting
confidence: 88%
“…Previous meta‐analyses have consistently demonstrated that ChEIs have beneficial effects on neuropsychiatric symptoms (Trinh et al , 2003; Hansen et al , 2008; Lockhart et al , 2011; Tan et al , 2014; Wang et al , 2014). However, differences in efficacy between each ChEI were inconsistent.…”
Section: Resultsmentioning
confidence: 99%
“…For memantine, one meta-analysis4 found that it improved behaviour symptoms while two4 6 did not demonstrate that. In addition, donepezil,4 galantamine5 and metrifonate7 were all proved to have significant effect on neuropsychiatric symptoms in early studies. However, in current meta-analysis, only galantamine was verified beneficial for neuropsychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in cholinergic neurotransmission are believed to be central to the development of AD 7 and the efficacy of AChI for stabilizing cognitive function has been directly related to central effects on acetylcholinesterase function 8, 9 . However, patients with AD can also often develop behavioral impairments, such as agitation and irritability; often these are the most troublesome symptoms for the caregivers 10, 11 . There are no FDA approved drugs for behavioral and psychological symptoms in any dementias but there is often off-label use.…”
Section: Introductionmentioning
confidence: 99%
“…There are no FDA approved drugs for behavioral and psychological symptoms in any dementias but there is often off-label use. There is some evidence that donepezil and Memantine have some benefit on behavioral and psychological symptoms in AD 11,12 but often psychiatric medications including antipsychotics, antidepressants, and anxiolytics are used off-label to treat behavioral symptoms at all levels of disease severity 13, 14 .…”
Section: Introductionmentioning
confidence: 99%